The Behavioural Dimension Of Sme’s Owner On Affecting The Financial Decisions - Bayu Sindhu Raharja; Nia Kurniati Bachtiar; Muhammad Ridhwan Ab. Aziz (Vilnius Gediminas Technical University, 2024)
Indexed by Scopus/ERA